Thermal properties and product distribution from pyrolysis at high heating rate of Naomaohu coal. (15th May 2021) - Chen, Tianju; Zhang, Ke; Zheng, Mo; Yang, Shuangxia; Yellezuome, Dominic; Zhao, Ruidong; Liu, Guangrui; Wu, Jinhu
Abstract: The thermal properties of Naomaohu (NMH) coal pyrolysis was investigated at heating rates of 100, 200, 400, and 1000 °C min −1 using a thermogravimetric analyzer coupled with an online Fourier transform infrared spectrometry analyzer (TG-FTIR) in this research. In addition, the effects of temperature on product distribution, including gas composition and the chemical compounds of coal tar, from pyrolysis of NMH coal via a fixed-bed reactor are analyzed using a gas chromatograph (GC) and gas chromatograph-mass spectrometry (GC–MS), respectively. The results show that the absorbance of the volatile species released is affected by the temperature and heating rates due to the difference in the cleavage and chain scission mechanisms from the thermal decomposition of NMH coal. The volatile species are released at a faster speed, indicating that the coal sample decomposed in a shorter residence time at higher heating rates. The GC–MS analysis of coal tar showed that most of the chemical compounds detected were phenolic compounds. Since the reactions at high heating rates are closer to industrial application, this research will provide a useful guideline for the thermal conversion characteristics of low-rank coal.